Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, dan Kecerdasan Spiritual Pemilik Pada Kinerja Usaha Mikro Kecil Menengah - Wijaya, Rio Surya; Sukartha, I Made (E-Jurnal Akuntansi, 2018)
National development of a nation includes economic development and Micro, Small and Medium Enterprises (MSMEs). MSME performance needs to be examined because the contribution of the MSME sector to the Gross Domestic Product (GDP) has increased from 57.84% to 60.34% in the last 5 years. This study aims to determine the effect of intellectual intelligence, emotional intelligence, and spiritual intelligence of the owner on the performance of Micro, Small and Medium Enterprises. Research subjects are the performance of UMKM in Denpasar City. The sample determination technique used in this study is Probably sampling used using a simple random technique. There are 100 MSMEs as samples with a questionnaire statement totaling 71 statements. Based on the results of the analysis of research obtained intellectual intelligence has a positive influence on the performance of MSMEs, Emotional Intelligence has a positive influence on the performance of SMEs, and Spiritual Intelligence has a positive influence on the performance of SMEs. Keywords : Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence.